Emergence of HBV resistance to lamivudine (3TC) in HIV/HBV co-infected patients in The Gambia, West Africa. - Stewart, B; Jobarteh, M; Sarge-Njie, R; Alabi, A; de Silva, T; Peterson, K; Peterson, I; Whittle, H; Rowland-Jones, S; Jaye, A; Cotten, M; Mendy, M (BioMed Central, 2011)
BACKGROUND: Lamivudine (3TC) is a potent inhibitor of both Hepatitis B virus (HBV) and Human Immunodeficiency Virus (HIV) replication and is part of first-line highly active antiretroviral therapy (HAART) in the Gambia. Unfortunately, the effectiveness of 3TC against HBV is limited by the emergence of resistant strains. AIM: The aim of this retrospective study was to characterise 3TC-resistant mutations in HBV from co-infected patients receiving HAART, by generating HBV polymerase sequence data and viral loads from HBV genotype E infected patients, both at initiation and during a course of 3TC therapy. METHOD: Samples from 21 HBV chronic carriers co-infected with HIV-1 (n = 18), HIV-2 (n = 2) and HIV-dual (n = 1) receiving HAART for a period of 6-52 months were analysed for the emergence of 3TC-resistance mutations. FINDINGS: Sixteen out of 21 HBV/HIV co-infected patients responded well to HAART treatment maintaining suppression of HBV viraemia to low (≤ 104 copies/mL) (n = 5) or undetectable levels (< 260 copies/ml) (n = 11). Out of the 5 non-responders, 3 had developed 3TC-resistant HBV strains showing mutations in the YMDD motif at position 204 of the RT domain of the HBV polymerase. One patient showed the M204V+ L180M+ V173L+ triple mutation associated with a vaccine escape phenotype, which could be of public health concern in a country with a national HBV vaccination programme. All except one patient was infected with HBV genotype E. CONCLUSIONS: Our findings confirm the risk of 3TC mutations in HAART patients following monotherapy. This is a novel study on 3TC resistance in HBV genotype E patients and encourage the use of tenofovir (in association with 3TC), which has not shown unequivocally documented HBV resistance to date, as part of first-line therapy in HIV/HBV co-infected patients in West Africa.HBV- hepatitis B infection; HIV- human immunodeficiency virus; HAART- antiretroviral therapy.